Confronting "Death on Wheels" : Making Roads Safe in Europe and Central Asia - World Bank (Washington, DC, 2017)
This report provides an overview of the challenges and opportunities in addressing road safety in the Europe and Central Asia (ECA) region. It presents information on the size, characteristics, and causes of the problem; presents evidence on the effectiveness of measures that countries world-wide have adopted to improve road safety; briefly describes current international road safety policy; and discusses a range of strategies and actions that could be undertaken by the World Bank in coordination and partnership with the World Health Organization (WHO), multilateral development banks, other international agencies and donors, as well as with private and civil society institutions. A primary audience of this report is internal-particularly managers and staff of the World Bank working in the transport, health, education, and governance sectors, to raise awareness about the multisectoral nature of the road safety challenge and of effective options to address it. It proposes ways that the World Bank might engage more to support ECA countries in tackling this issue, working in partnership with other international agencies and donors. The secondary audience is external policymakers, senior analysts, program managers, and their advisers in the governments of ECA countries, private sector officials, and civil society and international organizations working in this field. The goal is to support discussion on appropriate choices and instruments for advancing the road safety agenda as a top development priority over the short and medium term.